2012
DOI: 10.4329/wjr.v4.i12.455
|View full text |Cite
|
Sign up to set email alerts
|

Safety of bronchial arterial embolization with n-butyl cyanoacrylate in a swine model

Abstract: AIM:To compare the efficacy and safety of bronchial artery embolization (BAE) with n-butyl cyanoacrylate (NBCA) and gelatin sponge particles (GSPs). METHODS:Six healthy female swine were divided into two groups to be treated with BAE using NBCAlipiodol (NBCA-Lp) and using GSPs. The occlusive durability, the presence of embolic materials, the response of the vessel wall, and damage to the bronchial wall and pulmonary parenchyma were compared. RESULTS:No animals experienced any major complication. Two days later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Table 1 , Table 2 and Table 3 report the main quantitative data in studies of dogs, swine, and rabbits, respectively. Three articles, on primate and rat models, were not considered for the quantitative evaluation, which thus relied on 33 articles [ 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 , Table 2 and Table 3 report the main quantitative data in studies of dogs, swine, and rabbits, respectively. Three articles, on primate and rat models, were not considered for the quantitative evaluation, which thus relied on 33 articles [ 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“… 14 By contrast, NBCA polymerizes and forms a cast in the blood vessel. 15 , 16 , 17 , 18 This cast fills and adheres to the inner lumen of the blood vessel, thereby preventing blood flow and resulting in thrombus formation. 17 In this study, NBCA cast adhesion was observed in nine (56.25%) of the large (>500 μm) portal veins.…”
Section: Discussionmentioning
confidence: 99%
“…However, NBCA has been reported to induce acute vasculitis, and ethanol causes cell damage by deprivation of intracellular fluid and coagulation necrosis of the vascular wall and organ parenchyma [ 9 , 60 , 61 , 62 , 63 ]. Combining these two potentially highly irritating molecules may therefore be of concern.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%